2020
DOI: 10.1183/13993003.00716-2019
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A from innate and adaptive lymphocytes contributes to inflammation and damage in cystic fibrosis lung disease

Abstract: BackgroundElevated levels of IL-17A were detected in the airways of patients with cystic fibrosis (CF), but its cellular sources and role in the pathogenesis of CF lung disease remain poorly understood. The aim of this study was to determine the sources of IL-17A and its role in airway inflammation and lung damage in CF.MethodsWe performed flow cytometry to identify IL-17A-producing cells in lungs and peripheral blood from CF patients and β-epithelial Na+ channel transgenic (Scnn1b-Tg) mice with CF-like lung d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“… 21 We have recently identified IL‐17A secretion by Th cells, CD8 + T cells and several innate lymphocyte populations, that is γδ T cells, iNKT and innate lymphoid cells, in cystic fibrosis (CF) patients. Moreover, we were able to assign a critical role for IL‐17A secretion in the development of airway inflammation and pulmonary tissue destruction in CF‐like murine lung disease, 22 suggesting mechanisms by which IL‐17A might critically contribute to progression towards end‐stage disease in CF.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“… 21 We have recently identified IL‐17A secretion by Th cells, CD8 + T cells and several innate lymphocyte populations, that is γδ T cells, iNKT and innate lymphoid cells, in cystic fibrosis (CF) patients. Moreover, we were able to assign a critical role for IL‐17A secretion in the development of airway inflammation and pulmonary tissue destruction in CF‐like murine lung disease, 22 suggesting mechanisms by which IL‐17A might critically contribute to progression towards end‐stage disease in CF.…”
Section: Introductionmentioning
confidence: 83%
“…Sample acquisition was approved by the local ethics committee (Ethical approval #2700‐2015). Twenty‐one of the 23 CF samples were subjected to additional analyses published elsewhere 22 . LN from lung donors (LD) was obtained from the donor trachea during lung transplantation as described in the first paragraph of the Results section.…”
Section: Methodsmentioning
confidence: 99%
“…tuberculosis HN878 [ 43 ], whereas IL-17-producing T cells are associated with immunopathology and inflammation in patients with multidrug-resistant TB [ 44 ]. Moreover, IL-17A and IL-17A-mediated immune responses are highly related to lung damage caused by aberrant inflammation in various pulmonary diseases, such as COPD [ 13 ] and CF [ 14 ]. In M .…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin (IL)-17A and IL-17A-mediated immune responses are also related to lung damage caused by aberrant inflammation in various pulmonary diseases, such as COPD [ 13 ] and CF [ 14 ]. IL-17A exaggerates inflammatory responses in respiratory epithelial cells [ 15 ] and promotes the expression of α-smooth muscle actin and the production of profibrotic factors in fibrocytes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst this review does not permit us to examine all potential biomarkers in detail, the Biomarker Special Interest Working Group published a review highlighting neutrophil elastase, IL-8, TNF-α and IL-1β as valid biomarkers of lung inflammation. Other potential biomarkers such as Il-6, calprotectin, SPLUNC1 and calprotectin in serum, and HMGB-1 and YKL-40 in sputum require further evaluation [86] , [87] , [88] , [89] . The STOP-OB study showed that the Chronic Respiratory Infection Symptom Score (CRISS) in PwCF treated for PExs improved and exceeded the minimal important difference in almost 94% of the included patients, suggesting this could be a very useful tool in the evaluation of PExs [90] .…”
Section: Pulmonary Exacerbationsmentioning
confidence: 99%